Risk Factors and Protective Factors for COVID-19 Infection among Patients Visiting University Health Centre of Vadodara District: A Case Control study - Reetika Ranjan; Sangita V Patel; Sonal Mishra (Indian Association of Preventive and Social Medicine, 2023)
Introduction: Identification of risk factors and protective factors of COVID-19 can help in controlling the disease in healthcare and the community. Objective: To determine the risk factors and protective factors of COVID-19 among patients visiting University Health Centre of Vadodara district. Method: A case control study was done at University Health Centre of the district. Hundred cases who were COVID-19 positive by RTPCR/RAT testing and 100 controls who were RTPCR/RAT negative and never displayed its signs and symptoms were asked about knowledge of parameters such as hand hygiene, social distancing, any ayurvedic or homeopathic medicine intake, chemoprophylaxis of HCQ, visit to public places, any travel history outside city, state or country, the manner, place, and type of masks used by them to know the risk and protective factors for COVID-19. Results: Significant risk factors for COVID-19 infection based on logistic regression were increasing age (OR=3.65, p=0.004), higher education (OR=4.72, p=0.001), self-medication of homeopathic or ayurvedic medicines (OR=6.27, p=0.005). Significant protective factors for COVID-19 infection based on logistic regression were regular use of mask (OR=0.03, p=<0.0001), correct technique of mask use (OR=0.17, p=0.02), and maintaining social distance (OR=0.18, p=0.049). Conclusion: This study revealed the factors associated with occurrence of COVID-19 were increasing age, higher education, self- medication and factors which protect from infection were regular use of mask, correct technique of mask use, and maintaining social distance.